To calculate \(-\frac{12}{7} + \frac{3}{14}\), we need to find a common denominator for the fractions. The denominators are 7 and 14. The least common denominator (LCD) is 14.
Next, we convert \(-\frac{12}{7}\) to a fraction with a denominator of 14:
\[ -\frac{12}{7} = -\frac{12 \times 2}{7 \times 2} = -\frac{24}{14} \]
Now we can add the two fractions:
\[ -\frac{24}{14} + \frac{3}{14} = \frac{-24 + 3}{14} = \frac{-21}{14} \]
Next, we need to simplify \(\frac{-21}{14}\). Both the numerator and denominator can be divided by their greatest common divisor, which is 7:
\[ \frac{-21 \div 7}{14 \div 7} = \frac{-3}{2} \]
Thus, the final answer as a reduced improper fraction is:
\[ \boxed{-\frac{3}{2}} \]